Prognostic Significance of baseline systemic inflammation markers in PD-L1-negative advanced non-small cell lung cancer patients treated with the BRICS sequential regimen - Chen, Jianxin; Lin, Ming; Wang, Jian; Wang, Junhui; Peng, Yonghai; Yu, Zongyang (Frontiers in Immunology, 2025)
BackgroundNon-small cell lung cancer (NSCLC) remains a leading cause of cancer mortality, with PD-L1-negative tumors exhibiting poor response to immune checkpoint inhibitors (ICIs) and chemotherapy. The multimodal BRICS regimen-integrating stereotactic body radiotherapy (SBRT), Bifidobacterium supplementation, low-dose chemotherapy, and PD-1 blockade—offers a promising approach for this high-risk subgroup. This study evaluates the prognostic role of baseline systemic inflammation markers in this context.MethodsA retrospective analysis included 23 PD-L1-negative (TPS <1%), EGFR/ALK wild-type advanced NSCLC patients treated with BRICS (2018–2024). Pretreatment markers (e.g., CLR, LDH) were assessed from blood samples. The sequential regimen involved: (1) SBRT (24 Gy/3 fractions); (2) oral probiotics (6 g/day); (3) nab-paclitaxel (200 mg); and (4) anti-PD-1 antibody over six 21-day cycles. Primary endpoints were progression-free survival (PFS) and overall survival (OS), analyzed via Cox regression and Kaplan-Meier curves.ResultsEfficacy outcomes were robust: objective response rate 74.0%, disease control rate 95.7%, median PFS 16.0 months (95% CI: 9.11–22.89), and median OS 32.7 months (95% CI: 11.53–53.87). Univariate analysis showed elevated CLR predicted increased progression risk (HR = 2.907, p=0.04) and death risk (HR = 2.995, p=0.049), while high LDH correlated with worse PFS (HR = 3.448, p=0.013) and OS (HR = 3.016, p=0.041). Subgroup stratification confirmed shorter median PFS (7.10 vs. 20.0 months, p=0.008) and OS (9.20 vs. 36.20 months, p=0.031) for high LDH (≥250 U/L), and reduced PFS (14.20 vs. 19.10 months, p=0.032) and OS (17.70 vs. 36.20 months, p=0.038) for high CLR (≥10).ConclusionBaseline CLR and LDH are independent prognostic biomarkers for PD-L1-negative NSCLC patients receiving BRICS, reflecting systemic inflammation that may limit efficacy. These markers could optimize patient stratification and guide personalized therapy.